Novel REST Truncation Mutations Causing Hereditary Gingival Fibromatosis. (July 2021) - Chen, J.T.; Lin, C.H.; Huang, H.W.; Wang, Y.P.; Kao, P.C.; Yang, T.P.; Wang, S.K.
Hereditary gingival fibromatosis (HGF) is a rare genetic disorder featured by nonsyndromic pathological overgrowth of gingiva. The excessive gingival tissues can cause dental, masticatory, and phonetic problems, which impose severe functional and esthetic burdens on affected individuals. Due to its high recurrent rate, patients with HGF have to undergo repeated surgical procedures of gingival resection, from childhood to adulthood, which significantly compromises their quality of life. Unraveling the genetic etiology and molecular pathogenesis of HGF not only gains insight into gingival physiology and homeostasis but also opens avenues for developing potential therapeutic strategies for this disorder. Recently, mutations in REST (OMIM *600571), encoding a transcription repressor, were reported to cause HGF (GINGF5; OMIM #617626) in 3 Turkish families. However, the functions of REST in gingival homeostasis and pathogenesis of REST -associated HGF remain largely unknown. In this study, we characterized 2 HGF families and identified 2 novel REST mutations, c.2449C>T (p.Arg817*) and c.2771_2793dup (p.Glu932Lysfs*3). All 5 mutations reported to date are nonsenses or frameshifts in the last exon of REST and would presumably truncate the protein. In vitro reporter gene assays demonstrated a partial or complete loss of repressor activity for these truncated RESTs. When coexpressed with the full-length protein, the truncated RESTs impaired the repressive ability of wild-type REST, suggesting a dominant negative effect. Immunofluorescent studies showed nuclear localization of overexpressed wild-type and truncated RESTs in vitro, indicating preservation of the nuclear localization signal in shortened proteins. Immunohistochemistry demonstrated a comparable pattern of ubiquitous REST expression in both epithelium and lamina propria of normal and HGF gingival tissues despite a reduced reactivity in HGF gingiva. Results of this study confirm the pathogenicity of REST truncation mutations occurring in the last exon causing HGF and suggest the pathosis is caused by an antimorphic (dominant negative) disease mechanism.